Analisa Kesesuaian Program Corporate Social Responsibility terhadap Konsep Green SCM (Studi Kasus PT Kaltim Prima Coal) - Zella Windia Pratiwi; Aries Susanty (Industrial Engineering Online Journal, 2016)
Pertambangan merupakan salah satu industri yang sangat penting bagi keberlangsungan ekonomi suatu negara. Namun dalam pelaksanaannya banyak sekali isu-isu yang timbul akibat kegiatan pertambangan. Diperlukan upaya dalam penanganan isu tersebut dengan peningkatan kinerja lingkungan dan pelaksanaan tanggung jawab sosial (CSR). PT Kaltim Prima Coal telah melaksanakan CSR dengan baik. Dalam rangka rencana penutupan tambang, perusahaan ini ingin mengevaluasi pelaksanaan CSR secara lebih lanjut, namun proses evaluasi yang dilakukan hanya sebatas dalam pelaporan saja. Tulisan ini dibuat dalam menyelesaikan permasalahan yang ada di PT Kaltim Prima Coal sebagai indikator dalam proses evaluasi pelaksanaan tanggung jawab sosial dalam praktik green supply chain management (GSCM). Dalam tulisan ini dilakukan penilaian terhadap proram CSR dengan pembobotan menggunakan metode Rough Sets dan perhitungan  nilai kesesuaian program CSR terhadap konsep GSCM dilakukan dengan Fuzzy TOPSIS. Data untuk penelitian ini dikumpulkan melalui penelitian eksploratif dan pengisian kuisioner. Hasil pengolahan data menunjukkan bahwa program CSR yang paling sesuai dengan konsep GSCM adalah program Post Mining Area pada aspek sosial (0,428) dan aspek lingkungan (0,411) dan juga program Pencegahan Pencemaran pada aspek ekonomi (0,459). Usulan perbaikan akan dilakukan terhadap program Prima Nirbhaya (0,357), program Peningkatan Kapasitas Masyarakat (0,338), program Community Feedback System (0,333), program Coal Quality Management (0,332) dan Program Speak Up System (0,303).  ABSTRACTMining is one industry that is essential for the economic sustainability of a country. However, in practice a lot of issues that arise as a result of mining activities. Efforts are needed in the handling of these issues with improved environmental performance and the implementation of social responsibility (CSR). PT Kaltim Prima Coal has implemented CSR well. In order to mine closure plan, the company wants to evaluate the implementation of CSR further, but the evaluation process conducted merely reporting it. This paper was made in resolving the existing problems in PT Kaltim Prima Coal as an indicator in the process of evaluating the implementation of social responsibility in sustainable practices and practices of green supply chain management (GSCM). In this paper carried out an assessment of each program of social responsibility by weighting using sequencing methods Rough Sets and Fuzzy TOPSIS ranking with.   Data for this study were collected through exploratory research and filling the questionnaire.  From the results of this study will be obtained from the CSR program sequence that best suits GSCM practices to least appropriate. The result of data processing shows that the CSR program that best suits the GSCM practices is Post Mining Area program on the social aspects (0.428) and environmental aspects (0.411) and the Pollution Prevention program on economic aspect (0,459). Proposed improvements will be made to the Prima Nirbhaya program (0.357), Community Capacity Enhancement program (0.338), Community Feedback System program (0.333), Coal Quality Management program (0.332) and  Speak Up System program (0,303).